Renal involvement in sarcoidosis. Issue 538 (August 1970) - Lebacq, E.; Verhaegen, H.; Desmet, V.
Abstract : Among 152 sarcoidosis patients, 11% had hypercalcaemia, 62% had hypercalciuria and 13·8% had at least one renal stone. Impairment of renal function was mostly conspicuous in patients with hypercalcaemia. Twenty-five successful percutaneous renal biopsies were performed. Epithelioid granulomas were seen in ten cases, with inflammatory reaction more prominent than in other organs involved by sarcoidosis, due to simultaneous pyelonephritis. Thickening and hyalinization of capsular membrane and glomeruli as well as arterial walls were frequently encountered. Amyloid deposits could be seen in one case with chronic lung infection. Histopathological changes specific of sarcoidosis are related to an abnormal amount of serum gammaglobulins and calciuria exceeding 200 mg in 24 hr, which seem to be the best tests of involvement by the disease. Tubular reabsorption of calcium was low in two patients with hypercalciuria, which was corrected after corticosteroid treatment. High intestinal calcium absorption was lowered after hydrochlorothiazide had decreased urine calcium.